PENGARUH PENGAWASAN, LINGKUNGAN KERJA DAN DISIPLIN TERHADAP KESELAMATAN KESEHETAN KERJA PT. INDAH KIAT PULP AND PAPER KECAMATAN TUALANG KABUPATEN SIAK - Ridha Putri; Machasin '; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study was conducted to analyze the effect Supervision, Work Environment, the discipline of the Occupational Health Safety (K3) Employee at PT. Indah Kiat Pulp and Paper Perawang Variable in this study is the supervision, work environment, discipline and Occupational Health Safety (K3) while the population is all employees at PT. Indah Kiat Pulp and Paper Perawang totaling 1280 people. In the sampling, theauthor uses simple random sampling method, a total of 93 people. In this study, the data obtained will be processed by multiple linear regression model (multiple regression). Regression method can be used to show how the independent variables affect the dependent variable. From the research together have influence with the dependent variable. This means that control variables, the working environment and significant effect on the discipline of occupational safety and health of employees of PT. Indah Kiat Pulp and Paper Perawang. Monitoring the results of testing variables by t test showed surveillance, working environment and significant effect on the discipline of occupational safety and health of employees of PT. Indah Kiat Pulp and Paper Perawang.Keywords: Supervision, Work Environment, Discipline and Health and Safety